A construção da imagem de Hugo Chávez por documentários - Paiva, Gabriela Pandeló (2017)
The 90s in Venezuela consists in the decline of the Punto Fijo Pact, an agreement between the political elites to maintain the democratic order. In the Latin American context, this period, followed by the transition to the 21th century, can be represented by important events such as the rupture with a liberal economy and a change in the political scenario that became more interested with social issues, such as the fight against poverty. In Venezuela, the government of Hugo Chávez, a leader which support divided the nation, represents this political moment. With a controversial representation by many means of communication around the world, the aim of this research is to analyze how his image as president and leader of the Bolivarian Revolution is built. To fulfill these goals, the empirical material used are the following documentaries: "South of the Border" (Oliver Stone, 2010), "Mi Amigo Hugo" (Oliver Stone, 2014) e "Chavez: Inside the Coup" (Kim Bartleyl e Donnacha O'Briain, 2003). These films are imagetic documents pro-Chávez which registry will stay for posterity and its analysis will register the positive aspects of his legacy.